Economic Populist Sovereignism and Electoral Support for Radical Right-Wing Populism. (May 2022) - Mazzoleni, Oscar; Ivaldi, Gilles
Sovereignism is at the crux of the current wave of radical right-wing populism. Populist parties advocate 'taking back control' and generally do so in the name of the 'people', pledging to restore economic well-being. This article argues that populism and sovereignism are inherently connected in radical right-wing populism politics through a set of values that emphasize popular and national sovereignty. To test the empirical validity of our proposition, we focus on two established European radical right-wing populist parties, namely the Rassemblement National in France and the Swiss People's Party and use data from an original survey. We find that while Rassemblement National and Swiss People's Party voters diverge in general economic orientations, they share similar economic populist sovereignist values that significantly shape electoral support for those parties. These findings suggest that economic populist sovereignism may represent an important driver of support for the radical right-wing populism, alongside other correlates of radical right-wing populism voting, such as perceived immigration threat.